If I have a polynomial $f(x)$ and is divided by $(x- 3)$ and $(x + 6)$ the respective remainders are $7$ and $22$, what is the remainder when $f(x)$ is divided by $(x-3)(x + 6)$?

I tried it by doing:

$$f(x) =(x-3)(x+6)q(x) + ax+b $$ And, $a$ and $b$ comes out to be $-\dfrac53$ and $12$ respectively.

But I'm not sure how to solve any further. And kindly explain exactly how it's done

  • $\begingroup$ Chinese remainder theorem. $\endgroup$ – Wuestenfux Oct 12 '18 at 10:32
  • 2
    $\begingroup$ You got that the remainder is $-\frac53x+12$. What else do you want? $\endgroup$ – José Carlos Santos Oct 12 '18 at 10:33

Let $$f(x)=Q1(x-3)+7$$ and $$f(x)=Q2(x+6)+22$$ (where Q1 and Q2 are some functions of x, since degree of f can be 2)

So, if you substitute x=3 and x=-6 in above equations respectively, you get f(3)=7 and f(-6)=22

Now, let $$f(x)=Q3(x-3)(x+6)+(ax+b)$$ where (ax+b) is remainder
(remainder may be a constant or a linear in x because of degree restriction over f(x))

Substitute x=3 $$f(3)=0+(3a+b) $$ Substitute x=-6 $$f(-6)=0+(-6a+b)$$
So, 3a+b=7 and -6a+b=22

Solving, $$a= \frac{-5}{3}$$ and $$b=12 $$ Remainder is $$ \frac{-5x}{3}+12$$

  • $\begingroup$ In fact we can avoid solving equations - see my answer $\endgroup$ – Bill Dubuque Oct 13 '18 at 0:22

A slick way via $\ {ab\bmod ac = a(b\bmod c)} = $ mod Distributive Law, $ $ is to add $\ f(3) = 7\ $ to

$\quad f(x)\!-\!f(3)\bmod (x\!-\!3)(x\!+\!6)\, =\, (x\!-\!3)\Bigg[\dfrac{\overbrace{f(x)\!-\!f(3)}^{\Large\color{#c00}{ 22\ \ -\ \ 7}\ }}{\underbrace{x - 3}_{\large\color{#c00}{\Large -6\ -\ 3\ }\ \ }}\underbrace{\bmod_{\phantom{1_{1_1{1_{1_{1_1}}}}}}\!\!\!\!\!\!\!\!\!\!\! x\!+\!6}_{\Large\Rightarrow\ \ x\ \equiv\ \color{#c00}{-6}\!}\Bigg] =\, \color{#c00}{-\dfrac{5}3}(x\!-\!3) $

  • $\begingroup$ seems better, but a bit above my understanding...not so familiar with modular algebra... $\endgroup$ – idea Oct 13 '18 at 8:11
  • $\begingroup$ @omega The first linked post shows how to do it without mod. $\endgroup$ – Bill Dubuque Oct 13 '18 at 12:38

$f(x)=(x-3)a(x)+7\Rightarrow f(3)=7$

$f(x)=(x+6)b(x)+22\Rightarrow f(-6)=22$

If you can write $f$ is of the form $f(x) =(x-3)(x+6)q(x) + ax+b$.

Solution is so easy:

$$f(3)=3a+b=7$$ $$f(-6)=-6a+b=22$$

Hence, $a=-\dfrac53$ and $b=12$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.